Across the sub-Arctics of Canada [electronic resource] : a journey of 3, 200 miles by canoe and snow-shoe through the Hudson Bay region - Tyrrell, J. W. (James Williams), 1863-1945. (Toronto : W. Briggs, 1908)
Includes appendices. "Including a List of Plants collected on the way, a Vocabulary of Eskimo Words, and a Map showing the Route of the Expedition." Electronic reproduction. Mode of access: Internet. 44